ANALISIS KINERJA KARYAWAN TERHADAP PROMOSI JABATAN PADA PT. SELAMAT LESTARI MANDIRI KOTA SUKABUMI - Riani, Neneng Fitri; Mulia Z, Faizal; Sunarya, Erry (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.04.TAHUN 2020DO - 10.24843/EEB.2020.v09.i04.p05, 2020)
This study aims to find out and understand how much the analysis of employee performance toward the promotion of PT. Selamat Lestari Mndisi Sukabumi. This research uses a quantitative approach where data source are used a tool to obtain data. Sampel used by researchers as many as 75 empoyees the methods used by researchers are descriptive with associative approach. The result of the regression equation formed is Y = 3.061 + 1.043X. The result of the t test study on employee performance variables are 0.000 < 0,05 so that t count is 15,491. Each variable has a positive and sifnificant effect on analisis of employee toward job promotion.